Radioligands targeting P‐glycoprotein and other drug efflux proteins at the blood–brain barrier1. (24th April 2013) - Wanek, Thomas; Mairinger, Severin; Langer, Oliver
<x xml:space="preserve">Abstract</x> Brain penetration of radiopharmaceuticals or therapeutic drugs may be restricted by adenosine triphosphate‐binding cassette (ABC) transporters, such as P‐glycoprotein (Pgp), breast cancer resistance protein (BCRP), or the multidrug resistance‐associated proteins. These transporters are expressed in the luminal membrane of brain capillary endothelial cells forming the blood–brain barrier (BBB), where they actively efflux a wide range of chemically unrelated compounds from the brain back into the blood. Most efforts to visualize ABC transporters at the BBB with positron emission tomography have concentrated on Pgp. Pgp imaging probes can be classified as radiolabeled substrates or inhibitors. The radiolabeled substrates (R)‐[11C]verapamil and [11C]‐N‐desmethyl‐loperamide have been successfully used to assess Pgp function at the BBB of animals and humans. Radiolabeled Pgp inhibitors, such as [11C]tariquidar, [11C]elacridar, or [11C]laniquidar, were developed to measure Pgp expression levels at the BBB, which has so far remained unsuccessful as these probes were unexpectedly recognized at tracer concentrations by Pgp and BCRP as substrates resulting in low brain uptake. Studies on positron emission tomography tracers for other ABC transporters than Pgp (BCRP and multidrug resistance‐associated proteins) are still in their infancy. It is hoped that the experience gained with the imaging of Pgp will be successfully translated to the development of radiotracers to visualize other ABC transporters.Copyright © 2013 John Wiley & Sons, Ltd.